Effect of Invasion of Borrelia burgdorferi in Normal and Neoplastic Mammary Epithelial Cells - Gauri Gaur (MDPI AG, 2021)
Borrelia burgdorferi, the causative agent of Lyme Disease, is known to be able to disseminate and colonize various organs and tissues of its hosts, which is very crucial for its pathogenicity and survival. Recent studies have shown the presence of B. burgdorferi DNA in various breast cancer tissues, in some with poor prognosis, which raises the question about whether B. burgdorferi can interact with mammary epithelial cells and could have any effect on their physiology, including tumorigenic processes. As the model in this study, we have used MCF 10A normal and MDA-MB-231 tumorigenic mammary epithelial cells and infected both cell lines with B. burgdorferi. Our immunofluorescence and confocal microscopy results showed that B. burgdorferi is capable of invading normal epithelial and breast carcinoma cell lines within 24 h; however, the infection rate for the breast carcinoma cell lines was significantly higher. While the infection of epithelial cells with B. burgdorferi did not cause any changes in cell proliferation rates, it showed a significant effect on the invasion and migratory capacity of the breast cancer cells, but not on the normal epithelial cells, as determined by Matrigel invasion and wound healing assays. We have also found that the levels of expression of several epithelial–mesenchymal transition (EMT) markers (fibronectin, vimentin, and Twist1/2) changed, with a significant increase in tissue remodeling marker (MMP-9) in MDA-MB-231 cells demonstrated by quantitative Western blot analyses. This observation further confirmed that B. burgdorferi infection can affect the in vitro migratory and invasive properties of MDA-MB-231 tumorigenic mammary epithelial cells. In summary, our results suggest that B. burgdorferi can invade breast cancer tumor cells and it can increase their tumorigenic phenotype, which urges the need for further studies on whether B. burgdorferi could have any role in breast cancer development.